Analyzing instrument characteristics of critical thinking skills and mastery of concepts based on item response theory - M S Mu’iz; I Kaniawati; T R Ramalis (Pascasarjana Universitas Pendidikan Indonesia, 2018)
Studying aim is to exploration the instrument characteristics that can measure critical thinking skills (CTS) and mastery of concepts senior high school students by multiple-choice instrument in optic tools subject. The multiple-choice instrument will be analyzed about validity, reliability, item discrimination, item difficulty and item guessing factor based on item response theory (IRT). The multiple-choice instrument has 19 items measuring CTS such as interpretation, analysis, inference, evaluation and explanation. Together with measure cognitive processes dimension those are understand, applying, analyzing and evaluation. Moreover to measure knowledges dimension such as factual knowledge, conceptual knowledge and procedural knowledge. Subject and location of research are 40 students of senior high school 12 grade in South Banding region. They were selected using purposive sampling as participants of limited test. IRT counting is using add-ins irt for Microsoft Excel. The analysis results by IRT stated that instrument has been valid and reliable, as well every item has parameter-a, b and c scores. Thus, the multiple-choice assessment instrument fulfills quality test criteria and can measure CTS and mastery of concepts.